2001
DOI: 10.1111/j.1469-7793.2001.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of slow skeletal troponin I in adult transgenic mouse heart muscle reduces the force decline observed during acidic conditions

Abstract: Acidosis in cardiac muscle is associated with a decrease in developed force. We hypothesized that slow skeletal troponin I (ssTnI), which is expressed in neonatal hearts, is responsible for the observed decreased response to acidic conditions. To test this hypothesis directly, we used adult transgenic (TG) mice that express ssTnI in the heart. Cardiac TnI (cTnI) was completely replaced by ssTnI either with a FLAG epitope introduced into the N‐terminus (TG‐ssTnI*) or without the epitope (TG‐ssTnI) in these mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
2
45
2
Order By: Relevance
“…10 It has also been shown that the expression of slow skeletal troponin I in the heart of adult transgenic mice reduced the force decline observed under acidic conditions. 26 Another study showed that depressed troponin I protein phosphorylation was associated with the functional characteristics of a failing heart. 27 Those studies suggest that the sequential activation and expression of different isoforms of a contractile gene family might be the one of mechanisms of regulating contractile properties in the heart under various pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has also been shown that the expression of slow skeletal troponin I in the heart of adult transgenic mice reduced the force decline observed under acidic conditions. 26 Another study showed that depressed troponin I protein phosphorylation was associated with the functional characteristics of a failing heart. 27 Those studies suggest that the sequential activation and expression of different isoforms of a contractile gene family might be the one of mechanisms of regulating contractile properties in the heart under various pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…All transgenic TnT mice had approximately 50% of their endogenous TnT protein replaced with either WT or mutant human cardiac TnT (19,24). Expression of ssTNI (25) increased the pCa 50 to a similar extent as expression of TnT-I79N at baseline, and pCa 50 increased to an even higher extent after protein kinase A phosphorylation ( Figure 1B).…”
Section: Increased Incidence Of Ventricular Arrhythmias In Mice Exprementioning
confidence: 92%
“…We chose the slow skeletal isoform for these studies inasmuch as it is naturally expressed in the embryonic/neonatal period. Hearts of TG-ssTnI mice had slower relaxation kinetics, depressed effects of β-adrenergic stimulation [8], and protection against acidosis [9,10] and ischemia/reperfusion injury [11]. All of these properties are properties of preparations from neonatal rat hearts, and indicated that the special cardiac function in the neonatal period is importantly controlled by the isoform of TnI.…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%